Swedish Healthcare Managers and the Media – A Study of Strategies and Support During Mass Media Attention - Maria Wramsten Wilmar; Gunnar Ahlborg; Lotta Dellve; Inga Tidefors; Christian Jacobsson (Scandinavian Journal of Work and Organizational Psychology, 2017)
The aim of this study was to explore how Healthcare managers handle media attention focused on themselves or their organizations and the kind of support they seek and receive at such times. Altogether 40 persons were interviewed, of which 24 were managers with recent experiences of being the focus of mass media attention and 16 were people working with or otherwise familiar with the managers. Thematic analysis was used to extract themes from the data. The results showed that managers used both problem-focused coping such as openness and emotion-focused coping as avoidance of dealing with media representatives. The data implied that earlier experience of meeting the media influenced the coping with media attention, more positive experiences contributed to more openness. The openness strategy could be proactive or reactive, and the avoidance strategy could entail either avoiding information from media or contact with reporters. The managers identified several potential sources of social support that they seek within their organizations. However, receiving support from close actors within the organizations seldom occurred. The main support came from people who were particularly trusted by the managers as information specialists or family members. The findings contribute to an understanding for the complexity of interpersonal behavior and communication. It also makes us aware of the relevance of shared strategies with regard to communication with the media.